Effects of the A+ intervention on elementary-school teachers’ social and emotional competence and occupational health - Oliveira, Sofia; Roberto, Magda Sofia; Veiga-Simão, Ana Margarida; Marques-Pinto, Alexandra (Frontiers in Psychology, 2022)
Teaching is, to date, one of the most prone jobs to experiencing occupational stress and burnout. Owing to burnout’s negative personal, social, organizational and economic impacts, researchers, practitioners and education policy leaders are interested in developing practices and interventions aimed at preventing/reducing its prevalence. With teachers’ main professional demands to be of a social and emotional nature, interventions designed with a view to promote teachers’ social and emotional competence appears to be particularly promising, positively impacting teachers’ well-being and personal accomplishment and contributing to a decrease in their psychological distress, namely emotional exhaustion. However, theoretical and empirically grounded interventions with ecological validity and specifically targeting teachers are still scarce. Thus, to bridge the previously identified gaps, the present study aimed to evaluate the efficacy and the quality of the intervention’s implementation of the A+, an online social and emotional learning intervention for elementary-school teachers. A quasi-experimental study was conducted with a total of 81 participants (96.3% female, MAge = 46.21, SDAge = 4.82, n = 42 assigned to the experimental group) from three different school contexts. School clusters were similar in size, organizational structure and socioeconomic level, and as regards previous attendance at social and emotional learning interventions; however, they differed with regards to perceived organizational climate. Data on the efficacy of the A+ was collected across four waves using a set of self-report questionnaires that assessed proximal variables (i.e., social and emotional skills) and distal variables (e.g., well-being, burnout symptoms), and analyzed through Robust Linear Mixed-Effects Models. Coefficient omegas suggested adequate reliability of the measures. Additionally, two trained observers completed an observation grid to evaluate the quality of the A+ implementation (e.g., participant responsiveness, fidelity), with excellent inter-rater reliability. Results suggested that, over time, the A+ had positive impacts across proximal (e.g., increased self-regulation, positive relationship, conflict management skills) and distal variables (e.g., increased emotional well-being, decreased occupational stress and emotional exhaustion symptoms) favoring the experimental group. However, results differed across the school contexts. These findings were accompanied by good implementation quality indicators, namely high fidelity in the delivery of the A+ contents and high participants’ responsiveness. Despite its limitations, this study contributes to a growing body of research which reinforces the importance of investing in social and emotional learning interventions to prevent teachers’ burnout and improve their occupational health. Furthermore, it highlights the importance of implementation quality research as a component of program planning with a view to enhancing programs’ efficacy, as well as the need to adapt and consider context variables in research and practice.